Development of E-Module Based on the Traditional Puyuh Game on the Cooperation Character and the Tolerance of Elementary School Students - Syahrial Syahrial; Asrial Asria; Husni Sabil; Dwi Agus Kurniawan; Rahmat Perdana; Nurul Delima Kiska (Journal of Innovation in Educational and Cultural Research, 2022)
Electronic modules provide convenience for teachers and students in learning activities. This study aims to determine the feasibility or validity of the electronic module based on the traditional game "Puyuh" in learning activities and to determine the effect of implementing the electronic module on the character of cooperation and tolerance in students. The type of research used is development with a development model, namely 4D (Define, Design, Develop, and Disseminate). The sample of this study amounted to 50 students consisting of two classes. The data collection instruments are questionnaires and interviews. The data analysis used is descriptive qualitative and quantitative. The research results obtained are the electronic module based on the traditional game "Puyuh" which is feasible or valid to be used in learning activities. Electronic modules are an alternative in learning activities for teachers and students. The implementation of the electronic module based on the traditional game "Puyuh" has an influence on the character of cooperation and tolerance in students, besides that it can also introduce technology and preserve local wisdom in students.